Legal Certainty in Customary Jurisdictions (Case Study In Muara Batu District, North Aceh) - Afrizal, Teuku Yudi; Saifullah, T (SASI, 2023)
Introduction: Gampongs or villages in Aceh province are the only village-level government in Indonesia that is given the authority to resolve a number of civil and criminal cases through customary courts in gampongs.Purposes of the Research: This paper examines the legal certainty of customary court decisions in gampongs in the Muara Batu sub-district, North Aceh . The problems resolved in this paper are regarding the legal certainty of customary court decisions in gampongs and the extent to which gampongs in Muara Batu District implement customary justice in gampongs.Methods of the Research: This research is an empirical research. The data were collected from field data through interviews and observations as well as documentary data from legal writings.Results of the Research: The results of the research show that the decisions of the customary courts are binding and final. However, if the parties disagree with the customary court decision and seek legal proceedings, the customary court decision can become written evidence. In Muara Batu sub-district, each gampong has a customary court, but if they are related to minor crimes or jinayat, the gampong apparatus prefers to hand over the case to the authorities, if a peaceful process is not found. Except for cases of immoral khalwat and adultery committed in the gampong, the perpetrators are forced to marry or handed over to law enforcement to be processed according to jinayat law in Aceh.